Tools for Legislative Oversight: An Empirical Investigation - Pelizzo, Riuccardo; Stapenhurst, Frederick C. (World Bank, Washington, D.C., 2013)
Parliaments are the institutions through which governments are held accountable to the electorate. They have a wide range of tools with which to carry out this oversight function, but until recently little analysis had been undertaken on the characteristics or use of such tools. This paper uses data for 83 countries that was collected in 2001 to investigate whether the oversight potential relates to three variables, namely the form of government (presidential, semi-presidential, or parliamentary), per capita income levels, and the level of democracy. The paper finds that oversight potential is greatly affected by the form of government, per capita income levels, and levels of democracy. Countries with parliamentary forms of government, higher income levels, and which are more democratic have a greater number of oversight tools and greater oversight potential. While the oversight potential follows this general trend, the use of committees of enquiry, interpellations and ombudsman offices follows a different pattern. The use of interpellations as an oversight tool is most common in high income countries, less common in low income countries and least common in middle income countries while the presence of committees of enquiry and of the ombudsman offices is most common in middle income countries, less common in high income countries and least common in low income countries.